The Effectiveness of Social Inquiry Learning Model in Growing Students Sense of Nationalism in Social Studies: A Quasi-Experimental Study on Social Studies Subjects at SMP Muhammadiyah 6 Bandung - Junaedi, Meydi Ariyandini; Abdulkarim, Aim; Yulianti, Iing (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2023)
This study focuses on the use of social inquiry learning models based on the student's sense of nationalism in social studies subjects. The benefit of this research is to see the level of effectiveness of the use of learning models in fostering a sense of nationalism of students in social studies subjects. The theory of effectiveness & meaningful learning are used as the material for this study. The method used is a quasi-experimental research method with a quantitative approach. The location of the research was conducted at SMP Muhammadiyah 6 Bandung. The population in this study was class VIII students. The sample used was for the experimental class, namely VIII–A and the control class VIII–B using purposive sampling technique. In general, the results showed that the application of the social inquiry learning model was effective in fostering a sense of nationalism among students in social studies subjects. In particular, the results showed that there was a significant difference in results between the experimental class and the control class. Thus it can be concluded that the social inquiry learning model is effective in fostering a sense of nationalism in students of social studies subjects.